The Comparation Between Quality of Life of Patient with Uterine Prolapse which Choose Operative Therapy and Conservative Therapy at RSUD Dr. Moewardi Surakarta - ROSITA ALIFA PRANABAKTI (Nexus Kedokteran Klinik, 2016)
Introduction: Uterine prolapse is one of pelvic organ prolapse and become the number two most common cases after sistourethrokel . Epidemiology cases of uterine prolapse in Indonesia showed that uterine prolapse more common in patients grande multipara in menopause, rarely occurs in women nullipara . Over the past decade , the evaluation of pelvic organ prolapse in relation to health , using a comprehensive approach or overall. Instruments developed in this evaluation is the Prolapse Quality of Life Questionnaire (P-QOL). Differences in the treatment of uterine prolapse cases will certainly lead to different perceptions of individuals on their quality of life as measured using a P - QOL. The purpose of this study was to compare the quality of life of uterine prolapse surgery with conservative conducted in hospitals DR . Moewardi Surakarta . Methods: This study was observational analytic with cross sectional method . Samples were examined as many as 31 patients with uterine prolapse who were divided into 2 groups: 15 patients as operative group and 16 patients as conservative groups . Samples taken by accidental sampling . Samples were selected based on inclusion and exclusion criteria. Once approved informed consent, were interviewed using P - QOL questionnaire. The variables studied were the quality of life of patients in accordance with the chosen therapy . Data were analyzed using an unpaired t test Results: Obtained P values ??of 0.001 less than 0.05 . Meanwhile for the t table , look at the table t distribution with ? = 5 % : 2 = 2.5% with degrees of freedom ( df ) n - 2 or 31-2 = 29. By testing two sides ( significance = 0.025 ) results obtained for t table of 2.04. As for t obtained amounted to 3,81. Calculated t > t table ( 3.81 > 2.04 ) and P value ( 0.001 < 0.05), then Ho is rejected and H1 accepted, meaning that there are differences in the quality of life of patients with uterine prolapse between operative group with conservative groups . Conclusions: There are differences in the quality of life of patients with uterine prolapse surgery with conservative conducted at Hospital Dr. Moewardi Surakarta. Keywords: Uterine prolapse, quality of life, surgical, conservative.